A model of general anesthesia using modern muscle relaxants in one day surgery in children - E. M. Nasibova; R. Sh. Polukhov (Pediatric Anesthesia and Critical Care Journal, 2022)
Introduction In the last decade, there has been a widespread increase in interest in one-day surgery in children. The choice of the optimal model of anesthesia for minor surgery in chil- dren remains relevant to this day. Aim of the study: to conduct a comparative assessment of the potentiating ef- fect of modern inhalation anesthetics on the duration of muscle relaxants used in one-day surgery in children. Material and Methods The research was carried out in the surgical clinics of the AMU in the period from 2010 to 2020. The study in- cluded 156 children aged 0 to 16 years of age at risk of I- II ASA anesthesia, who were operated on in a planned manner under combined general anesthesia. In accord- ance with the requirements of the international program GCP (good clinical practice), all patients were included in the study only after receiving the voluntary consent of their parents. Results and Conclusions 1. A decrease in the main and maintenance doses of non-depolarizing muscle relaxants rocuronium bro- mide, atracurium and cisatracurium besylate under conditions of combined anesthesia with 1.3 MAC of isoflurane provides excellent and good conditions for tracheal intubation, high-quality intraoperative relaxation, regardless of the methods of performing surgical inter- ventions (traditionally or laparoscopically). 2. A single injection of 0.3 mg / kg rocuronium bro- mide, 0.3 mg / kg atracurium and 0.1 mg / kg cisa- tracurium besylate when combined with sevoflurane provide quality conditions for smooth tracheal intu- bation and mechanical ventilation in children of all age groups. The duration of the clinically effective action of the studied muscle relaxants in the indi- cated doses in children under 2 years of age makes it possible to provide high-quality relaxation during operations performed both traditionally and laparo- scopically for 30-50 minutes. To ensure comfortable working conditions for surgeons during laparoscopic operations in children over 2 years of age, the main doses of miorelaxants should be at least 0.4 mg / kg for atracuria, 0.12 mg / kg for cisatracurium and 0.45 mg / kg for rocuronium bromide.